2014
DOI: 10.2754/avb201483010019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine on functions of cooling-stored ram sperm in vitro

Abstract: Caffeine is a well-known sperm motility stimulator, however, its effects on cooling-stored ram semen are unknown. The aim of the study was to examine the effect of caffeine on selected motility and viability indices of cooling-stored ram spermatozoa. Sperm ejaculates from 4 rams were diluted (1:3) in a Triladyl extender. Samples were stored for 96 h at 4-5 °C in two sets. In the first set used for motility analysis, caffeine at concentrations of 1, 2 or 4 mmol·l -1 was added to sperm aliquots on the day of ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…The results of this study were contrary to those reported by Špaleková et al [45] who observed no effect on the acrosome integrity in frozen ram semen. This could be attributed to the dose of caffeine or the cryopreservation steps, including equilibration period and time of exposure to the caffeine addition.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study were contrary to those reported by Špaleková et al [45] who observed no effect on the acrosome integrity in frozen ram semen. This could be attributed to the dose of caffeine or the cryopreservation steps, including equilibration period and time of exposure to the caffeine addition.…”
Section: Discussioncontrasting
confidence: 99%
“…As a result of excessive ROS production that consequently leads to lipid peroxidation, decreased motility and viability and increased sperm morphological defects [52] . The caffeine enhances utilization of fructose [53] , and stimulates both respiration and sperm metabolism [45] .…”
Section: Discussionmentioning
confidence: 99%
“…These effects decrease fertilization capability up to 50% of spermatozoa during cryopreservation (Celeghini et al 2008) and reduce subsequent spermatozoa viability and the ability to fertilize an oocyte (Defoin et al 2008). The success of spermatozoa cryopreservation depends on many factors, including individuality (Härtlová et al 2013), the interaction between cryoprotectants and the extender type (Špaleková et al 2014;Stádník et al 2015), the length of cooling and equilibration period (Andrabi 2007), and the speed of freezing or thawing (Clulow et al 2008).…”
mentioning
confidence: 99%
“…The steps of producing insemination doses (diluting the sperm, filling the straws, cooling and freezing) have a significant effect on sperm motility after thawing (Siddique et al 2006). Especially, the properties of extender used (Crespilho et al 2012;Cao et al 2013;Špaleková et al 2014) and freezing methods are important (Watson 2000;Medeiros et al 2002).…”
Section: Reproduction Bull Sperm Extender Ldl Cholesterol Sperm Smentioning
confidence: 99%